Static balance ability of persons with visual impairment on firm and foam surfaces - Triloki Prasad; Subhankar Ghosh; Asis Goswami (European Federation of Adapted Physical Activity, 2020)
The Balance Error Scoring System (BESS) is an easily administered test of short duration static balance. In daily activities including sports, people with low vision (partially sighted) or partial blindness and visual impairment face difficulty while balancing their body in static positions. The purpose of this study is to test balance and stability of people with low vision or partially sightedness (PS) and full blindness (FB) using BESS test. The BESS was used to measure the error in the range from 0 for "excellent balance" and 10 for "very poor balance". A total of 106 volunteers participated in the study that included 43 PS (mean age = 17.5y, SD = 3.2y) and 63 FB (mean age = 20y, SD = 3.4y) volunteers. The test for the BESS was taken for Non-Dominant Leg (NDL) and Dominant Leg (DL). Descriptive statistics and non-parametric tests were carried out. The study revealed that all the combinations of correlation between Firm Surface (FS) and Foam Surface (FOS) were statistically significant at p<.05. Test of age, height, and weight of the PS and FB group indicated significant differences between the groups in these variables. Surface firmness is less effective in evaluating balance for persons with visual impairments.